The Translation and Interpretation of Sadr Al-dinshirazi’s “khalq Al-a’mal” Treatise - Malikov, Aladdin (Scholarya Demo Journal of Ruby, 2019)
Sadr al-Din Shirazi (1571-1640) occupies an important place in the history ofthe Eastern Islamic philosophy. Among the works of ten the most important andintellectual philosophers in the history of Islamic philosophy his heritage is themostly studied one. Shirazi is a philosopher famous for his unusual philosophicaland theosophical views. Shirazi’s “transcendental philosophy” relates to Isfahanphilosophical school and is greatly developed by its adherents. The works byS.Shirazi can be classified into three different groups. These are: 1. the commentsfor the Quran and hadiths; 2) the comments and references wnich have been writtenbefore him and already discussed in other philosophical books; 3) the works onphilosophy written by him as a founder of the Transcendental school ofphilosophy. The most important work from the third group is “Al-Asfar al arba’a al-’aqliyyah fi hikmat al-muta’aliyah” a book consisted of many volumes and issome kind of encyclopedia of the Islamic philosophy. The treatises written byS.Shirazi are covering many themes. An outstanding and deeply studied workdevoted to freedom of choice is “Hikmat Al-Ayn” work that means “Wisdom of aSource”. This is a work about Algebra and Will. According to our translation andinterpretation, S.Shirazi has accumulated the various philosophical conceptionsand basic theoretical views of the philosophers and thinkers who have lived beforehim, and has studied them accompanying with the arguments of his own. He writesabout the rights and obligations of the human being and about freedom of hischoice as well. Thus, he is unifying the various philosophical ideas combiningthem with his own concepts. In “Khalq al-a’mal” treatise he is marking out the four basic philosophicalconceptions. More specifically, he introduces three theories in the history ofphilosophy together with his arguments and formulating then the fourth theorywith comments which is rooted deeply in the scientific knowledge. That is whythe School of the Transcendental Philosophy considers this theory the highest,being superior to the previous three conceptions.